From Type II to Z-Scheme: A DFT Study of Enhanced Water Splitting in the SGa2Se/TeMoS Heterojunction - Fan Yang; Marie-Christine Record; Pascal Boulet (Crystals)
Harnessing solar energy for photocatalytic water splitting and hydrogen fuel production necessitates the development of advanced photocatalysts with broad solar spectrum absorption and efficient electron-hole separation. In this study, we systematically explore the potential of the SGa2Se/TeMoS heterojunction as a water-splitting photocatalyst using first-principles calculations. Our results indicate that while the heterojunction exhibits type-II band alignment, its band edge positions are inadequate for initiating water redox reactions. To overcome this limitation, we successfully engineered a Z-scheme SGa2Se/Zr/TeMoS heterojunction by incorporating a Zr layer to modulate the charge transfer mechanism between the SGa2Se and TeMoS layers. The potential positions of the HER and OER in this Z-scheme heterojunction overcome the limitation of the bandgap on water decomposition, allowing the optimized heterojunction to exhibit suitable band edge positions for water splitting across a wide pH range (0 ≤ pH ≤ 11.3), from acidic to weakly basic conditions. Additionally, the heterojunction exhibits exceptional light absorption capabilities across the entire spectrum, particularly in the infrared and visible regions, which greatly enhances the utilization of solar energy and highlights its potential as an efficient broad-spectrum photocatalyst for water splitting.